Contribution of iron and protein contents from rat brain subcellular fractions to MR phase imaging. Issue 5 (7th June 2016) - Leutritz, T.; Hilfert, L.; Busse, U.; Smalla, K.‐H.; Speck, O.; Zhong, K.
Abstract : Purpose: Investigation of magnetic susceptibility and chemical exchange as sources of MRI phase contrast between gray and white matter resulting from protein and iron content from subcellular fractions. Methods: This study analyzes the iron and macromolecule content of different subcellular fractions from rat brain and their relation to the water‐resonance frequency by NMR spectroscopy. Additionally, the contributions of susceptibility and exchange were determined with different NMR reference substances. Results: Only weak correlations between iron ( r  = 0.4318, P  = 0.76) or protein content ( r  = 0.4704, P  = 0.70) and frequency shift were observed. After membrane depletion, the correlation for iron increased to r  = −0.9006 ( P  = 0.0009), whereas the shift relative to protein content increased much less ( r  = −0.4982, P  = 0.64). Exchange‐driven frequency shifts were 1.283 ppb/(mg/ml) for myelin and 0.775 ppb/(mg/ml) for synaptosomes; susceptibility‐driven shifts were −1.209 ppb/(mg/ml) for myelin and −0.368 ppb/(mg/ml) for synaptosomes. The ratios between susceptibility and exchange differ significantly from simple protein solutions. Conclusions: As a result of counteracting susceptibility and exchange and increased relative shifts in membrane‐depleted fractions, we conclude that tissue microstructure accounts more for the in vivo phase contrast than in the situation of homogenized tissue. Thus, membranes may generate much of the in vivo MR phase contrast resulting from anisotropy. Magn Reson Med 77:2028–2039, 2017. © 2016 International Society for Magnetic Resonance in Medicine